2022
DOI: 10.1007/s40735-022-00643-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors Incorporated Into Water-Based Epoxy Coatings on Metals for Corrosion Protection: A Review

Abstract: Corrosion and its protection are one of the major challenges that are faced by the industries. To overcome this, new coatings with characteristic properties which are environmentally friendly are introduced. A cost-effective and most reliable way of corrosion protection is via barrier coatings, in which water-based epoxy coatings showed significant corrosion resistance. Although the epoxy coating creates a barrier between the metal and the corroding ions, there is a chance of leakage due to mechanical rupture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 101 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Structural solutions for the lost elements were taken in accordance with the drawings preserved according to historical references [18].…”
Section: Restoration Of the Sheet Rolling Shop And The Water Tower Wi...mentioning
confidence: 99%
“…Structural solutions for the lost elements were taken in accordance with the drawings preserved according to historical references [18].…”
Section: Restoration Of the Sheet Rolling Shop And The Water Tower Wi...mentioning
confidence: 99%
“…Water-based coatings are eco-friendly, chemically less smelling, and less expensive (Gadhave, Mahanwar and Gadekar, 2018). Also, water-epoxy hybrid coatings can be advantageous for fully exposed steel structures that provide corrosion resistance (Jomy, Prabhu and Prabhu, 2022). Although numerous studies on re retardant intumescent coatings have been conducted, very few sample studies were reported as per the British standard test procedures to meet the NBC criteria, which are the essential conditions for industrial development.…”
Section: Introductionmentioning
confidence: 99%
“…3 To tackle this challenge, twodimensional materials are incorporated into WECs to reduce coating porosity. 4,5 MXene, a novel two-dimensional material, has garnered considerable attention in the field of anticorrosion because of its impermeability and substantial specific surface area. 6−8 Yan et al proposed that epoxy coating containing MXene (Ti 3 C 2 T x ) exhibited enhanced corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, WECs may suffer from the formation of defects, such as micropores and microcracks due to the volatilization of water during the curing process, which results in poor anticorrosion properties . To tackle this challenge, two-dimensional materials are incorporated into WECs to reduce coating porosity. , …”
Section: Introductionmentioning
confidence: 99%